Question: 1 / 165

What is the solution for 8 - 4(x - 1) = 2 + 3(4 - x) when x=3, y=-4, and z=2?

-2

To solve the equation 8 - 4(x - 1) = 2 + 3(4 - x), we first need to substitute x = 3 into the equation.

Starting with the left side:

8 - 4(3 - 1) = 8 - 4(2) = 8 - 8 = 0.

Now for the right side:

2 + 3(4 - 3) = 2 + 3(1) = 2 + 3 = 5.

With both sides substituted, we have:

0 = 5, which shows that the equation does not hold true when x = 3.

However, the original question seems to imply using the expression 8 - 4(x - 1) = 2 + 3(4 - x) to evaluate the left and right sides for any given values of x.

When x = 3, indeed it simplifies as shown, confirming that the result we calculated aligns with potential solutions lying within the choices.

Upon further analysis considering offsets or patterns within multiple test evaluations, additional aspects of these values contribute to finding the final answer. Nevertheless, the net result invites you to consider how each manipulation conforms or conflicts

0

2

4

Next

Report this question